2011
DOI: 10.1111/j.1365-2133.2011.10561.x
|View full text |Cite
|
Sign up to set email alerts
|

Tattoo inks in general usage contain nanoparticles

Abstract: The finding of NPs in tattoo inks in general usage is new and may contribute to the understanding of tattoo ink kinetics. How the body responds to NP tattoo pigments should be examined further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 31 publications
5
88
0
4
Order By: Relevance
“…Previous reports have indicated that tattoo pigments in human skin stain the cytoplasm of fibroblasts deep in the dermis layer. 38,39 Tattoo dyes thus serve as in vivo THG contrast agents of fibroblasts in mouse and human skin in our studies. For a fair comparison, the intensities of the in vivo THG images were obtained under the same PMT voltage.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have indicated that tattoo pigments in human skin stain the cytoplasm of fibroblasts deep in the dermis layer. 38,39 Tattoo dyes thus serve as in vivo THG contrast agents of fibroblasts in mouse and human skin in our studies. For a fair comparison, the intensities of the in vivo THG images were obtained under the same PMT voltage.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…3(a)], the enhanced THG signals from the tattoo pigments [ Fig. 3(b) (arrows)], which provides the contrast of fibroblasts, 38,39 was revealed within the collagen network. The contrast of the collagen network was provided by the SHG signals.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Ponadto, mogą się w nich również znajdować duże ilości nanocząsteczek oraz ftalanów i węglowodorów, które mają działanie rakotwórcze i działają szkodliwie na gospodarkę hormonalną [9,10]. Czarny tusz do tatuażu zawiera różnego rodzaju węglowodory czy nanocząsteczki węgla.…”
Section: Wprowadzenieunclassified
“…Nevertheless, some researchers stress that the long contact time between skin and tattoos allows continued exposure to toxic or allergenic metals with consequent accumulation in the body. The potential diffusion of nanoparticles also remains speculative 10 . Tattoo pigments might be discharged from the body without any further health-related complications.It might be thought better off undergoing laser tattoo removal.…”
Section: Potential Links Between Tattoos and Skin Cancersmentioning
confidence: 99%